2006
DOI: 10.1007/s10654-006-9050-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between outdoor air pollution and emergency department visits for stroke in Edmonton, Canada

Abstract: Inconsistent results have been obtained from studies that have examined the relationship between air pollution and hospital visits for stroke. We undertook a time-stratified case-crossover study to evaluate associations between outdoor air pollution and emergency department visits for stroke among the elderly according to stroke type, season, and sex. Analyses are based on a total of 12,422 stroke visits among those 65 years of age and older in Edmonton, Canada between April 1, 1992 and March 31, 2002. Daily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 45 publications
8
119
1
2
Order By: Relevance
“…This may be because of over classification with the use of both primary and secondary discharge codes. However, an increase in cardiovascular and respiratory hospitalizations is consistent with the literature [8,16,24,50,66], though some literature has shown no increase in cardiovascular hospitalizations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or mortality [67]. Figure 4 displays the percent increase in hospital admissions for the haze period compared to the non-haze period in the affected region for all specific diagnoses of interest with single and distributed lag models.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This may be because of over classification with the use of both primary and secondary discharge codes. However, an increase in cardiovascular and respiratory hospitalizations is consistent with the literature [8,16,24,50,66], though some literature has shown no increase in cardiovascular hospitalizations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or mortality [67]. Figure 4 displays the percent increase in hospital admissions for the haze period compared to the non-haze period in the affected region for all specific diagnoses of interest with single and distributed lag models.…”
Section: Resultssupporting
confidence: 76%
“…While it is clear that local populations are affected by wildfire events, a growing concern is the potential health impact on geographically distant populations, specifically in susceptible groups such as the elderly. Epidemiologic research has identified the elderly, who are more likely to have pre-existing lung and heart diseases, as a population vulnerable to the effects of short-term exposures to air pollution including fine particles [24,[40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…We fitted air pollutants using lag 0-2 (mean of the concurrent day and 2 previous days) based on evidence from published Canadian studies. [32][33][34] We chose daily mean air temperature as our primary exposure, because it represents the exposure throughout the entire day and night. 13 Cold and heat were separately analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, an 11% (95% CI, 1-22%) increase in stroke risk in exposed patients with diabetes [88]. A large case-crossover study found an association between other components of air pollution (NO2 and CO) and cerebrovascular disease, but no correlation was noted with changing PM levels [89]. Similarly, a large registry of first-ever strokes found no association with PM 10 for ischemic or hemorrhagic stroke [90].…”
Section: Pm and Cerebrovascular Health Effectsmentioning
confidence: 98%